2019
DOI: 10.1111/medu.13905
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for complexity in medical education: a model of adaptive behaviour in medicine

Abstract: Context Medicine is practised in complex systems. Physicians engage in clinical and operational problems that are dynamic and lack full transparency. As a consequence, the behaviour of medical systems and diseases is often unpredictable. Medical science has equipped physicians with powerful tools to favourably impact health, but a reductionist approach alone is insufficient to optimally address the complex challenges posed by illness and public health. Concepts from complexity science, such as continuous quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 124 publications
1
39
0
Order By: Relevance
“…He asserts that a systematic approach ‘fails to provide the flexibility and leverage of diverse perspectives (systems approach) required to solve complex problems’. For instance, privileging systematic over systems approaches might be the catalyst of a ‘healthcare system that is plagued by fragmented care’ . As researchers interested in teamwork and complexity, we echo Woodruff's sentiment.…”
mentioning
confidence: 81%
“…He asserts that a systematic approach ‘fails to provide the flexibility and leverage of diverse perspectives (systems approach) required to solve complex problems’. For instance, privileging systematic over systems approaches might be the catalyst of a ‘healthcare system that is plagued by fragmented care’ . As researchers interested in teamwork and complexity, we echo Woodruff's sentiment.…”
mentioning
confidence: 81%
“…Through reflective practices, case-based discussions and simulation scenarios as a group, these influence intrinsic motivation (using group MI techniques) as well as increase technical expertise ("intrinsic characteristics") both working alongside each other. Through the sharing of experiences and peer norming, this promotes a sense of a common purpose ("attractor") which then leads to an increase in the capacity to collectively adapt ("adaptive capacity") (Woodruff 2019). This is followed by process mapping discussions around staff and patient feedback.…”
Section: Model Frameworkmentioning
confidence: 99%
“…Other contributing factors are social (Wailling et al, 2020), cultural (Braithwaite et al, 2017), and historical (Classen et al, 2011). Woodruff suggests that we cannot solve complex problems using a reductionist paradigm because complexity exists within all layers of the healthcare system and affects the efforts of clinicians and policy makers to improve and reconcile individuals' healthcare experience, population outcomes and healthcare costs (Woodruff, 2019). To better account for the complex nature of medicine, such systems should instead be viewed through a "complex adaptive systems framework" (CAS).…”
Section: Introductionmentioning
confidence: 99%
“…These assumptions do not seem to hold up in reality as research has consistently shown that teachers do not readily accept new technologies and, even when they do, technologies are used to support existing teaching practice rather than to exploit new pedagogies 8,9 . This reductionist conceptualisation of learning technologies as a solution fails to acknowledge that medicine, and therefore medical education, operates as a complex adaptive system where even a well‐defined intervention may lead to unexpected outcomes or system‐wide behaviours 10 . A structured appreciation of influences of change in complex adaptive systems is undoubtedly necessary to more effectively implement change in medical education 11 …”
Section: Introductionmentioning
confidence: 99%